Вы находитесь на странице: 1из 4

Recursive sequences

1.

ak 2ak+1 + ak+2 0

2 j1

(a

k = 2 i 1

(a
n

j=i

2a k +1 + a k + 2 ) 0 a 2i1 a 2i a 2 j + a 2 j+1 0 a 2i1 + a 2 j+1 a 2i + a 2 j

2 i 1 + a 2 j+1 ) (a 2 i + a 2 j )
n

j=i

(n i + 1)a 2i 1 + (a 2i+1 + a 2i +3 + ... + a 2 n +1 ) (n i + 1)a 2i + (a 2i + a 2i + 2 + ... + a 2 n ) = (n i + 2 )a 2i + (a 2i + 2 + ... + a 2 n )


n

i =1

[(n i + 1)a 2i1 + (a 2i+1 + a 2i+3 + ... + a 2n +1 )] [(n i + 2)a 2i + (a 2i+2 + ... + a 2 n )]
n

i =1

On expanding and grouping terms on L.H.S. and R.H.S., we have


n[a 1 + a 3 + ... + a 2 n +1 ] (n + 1)[a 2 + a 4 + ... + a 2 n ]

a 1 + a 3 + ... + a 2 n +1 a 2 + a 4 + ... + a 2 n

n +1
n

If the numbers are in A.P., then ak 2ak+1 + ak+2 = 0 .


By the first part of this question, replacing in the procedure all inequalities by equality, result follows.
Put a1 = 1,

a k = t k 1 , then

ak 2ak+1 + ak+2 =
Applying

2.

i = 1,2,..., n
i = 1,2,..., (n + 1)

t k 1 2 t k + t k +1 = t k 1 1 2 t + t = t k 1 1 t

a 1 + a 3 + ... + a 2 n +1
n +1

1 + t + t 2 + ... + t n
>
n +1

a = t 2i 1 = t i1 t ,
2i
a 2i1 = t 2i2 = t i 1 ,

a 2 + a 4 + ... + a 2 n
n

>0,

since 0 < t < 1 .

t + t t + t 2 t + ... + t n 1 t 1 + t + t 2 + ... + t n 1
=
t
n
n
1 t n +1

1 t n +1
1 t n
t
>
(n + 1)(1 t ) n(1 t )

>

n +1

1 tn
n

a + 5 32 + 5 7
7
14 5 3 5
a2 = 1
=
= a2 5 = 5 =
=
2a 1
23 3
3
3
23
2

n = 1,

We like to use mathematical induction to prove the given proposition.


For

(3 5 )
5<
(2 5 )

0 < a2 5

The proposition is true for n = 1 .

a2

and

21 1

2
3 5
< 6 2
= 2 5
2 5
11

(3 5 )
5<
(2 5 )

2k 1

Assume that the proposition is true for n = k . i.e.

0 < ak

2k 1 1

2k

2
< 6 .
11

We would like to prove that the proposition is true for n = k + 1 .

a +5
a 5
a k +1 5 = k
5= k
2a k
2a k
2

> 0 , since ak > 0 .

(a
5=

a k +1

( )
(2 5 )

5 3 5
ak

5
2a k

2 k +1

2 k +1 1

(3 5 )
(2 5 )

2 k +1

2 k +1 1

( )
( )

1 3 5
<
k 1
2a k 2 5 2 1

(3 5 )
<
(2 5 )

k 1

, by inductive hypothesis.

2 k +1

3 5

= 2 5
2 5

2 k +1

ak < 5 .

, since by inductive hypothesis

2 k +1 1

2
< 6
11

2 k +1

The proposition is true for n = k + 1.

By the principle of mathematical induction, the proposition is true n


3.

(i)

yk = Ayk-1 + B

k 1

k 1

i =1

i =1

(y i+1 y i ) =

A k 1 1
B
A 1

k 1
A k 1 1
(y 2 y1 ) y k y1 = A 1 [Ay1 + B y1 ]
A 1
A 1

can also be proved by mathematical induction.

xk = (a + b) xk-1 ab xk-2

(b)

A i 1 (y 2 y1 ) y k y1 =

k 1
k 1
A k 1 1
[(A 1)y1 + B] + y1 = A k 1 1 y1 + A 1 B + y1 = A k 1 y1 + A 1 B
A 1
A 1
A 1

y k = A k 1 y1 +

(a)

yk-1 = Ayk-2 + B

yk yk-1 = A(yk-1 yk-2) = A2(yk-2 yk-3) = = Ak-2 (y2 y1)

yk =

(ii)

and

(k 2)

xk axk-1 = b(xk-1 axk-2) = b2 (xk-2 axk-3) = = bk-1(x1 ax0)

xk axk-1 = bk-1(x1 ax0)

xk = axk-1 + bk-1(x1 ax0) .

Then by (i), Let A = a and B = bk-1(x1 ax0)


x k = a k 1 x 1 +

(iii) Let

xk = (a + b) xk-1 ab xk-2

(k 2), then by comparing coefficients,

(a, b) = 2 , 1

Solving we get

If

a k 1 1 k 1
b (x 1 ax 0 )
a 1

or

(a, b) = 1,

1
2
a + b = , ab =
3
3

2

3

(a, b) = 2 , 1 , applying (ii) (b), we have


3

k 1

2
1
k 1
a 1 k 1
3 k 1
2
2
x k = a k 1 x 1 +
b (x 1 ax 0 ) = x 1 +
1 x 1 x 0
a 1
2
3
3
1
3
1
2 3
2 3
2
lim x k =

x + x = x + x = x + x
k
2 1 3 0 5 1 3 0 5 1 5 0
1+
3

If

(a, b) = 1,

k 1

2
, lim x k does not exist and is rejected.
3 k
2

4.

Let P(n) be the proposition


For

( 3 + 1) = a
1

P(1),

Assume P(k)
For

3 + 1 = a n 3 + bn

3 + b1 ,

is true for some

where a1 = 1, b1 = 1.
. . i.e. .

( 3 + 1)

P(1)

= a k 3 + bk

(1)

P(k + 1) .

( 3 + 1)

( 3 + 1) ( 3 + 1)

where

a k +1 = a k + b k ,

k +1

(a

by (1)

3 + bk

)( 3 + 1) = (a

+ b k ) 3 + (3a k + b k ) = a k +1 3 + b k +1

b k +1 = 3a k + b k

P(k + 1) is true.

By the principle of mathematical induction, the proposition is true n

(i)

is true.

a n+2 3 + b n+2 =

( 3 + 1)

n+2

( 3 + 1) ( 3 + 1) = ( 3 + 1) [2( 3 + 1)+ 2] = 2( 3 + 1)
n

] [

n +1

+ 2 3 +1

= 2 a n +1 3 + b n +1 + 2 a n 3 + b n = [2(a n +1 + a n )] 3 + [2(b n +1 + b n )]

(ii)

an+2 = 2(an+1 + an)

Let P(n) be the proposition


For

P(1),

P(k + 1) .

3 1

5.

(i)

3 1 = ( 1) n 1 a n 3 b n

( 3 + 1) ( 3 1) = [a

is true for some

)(

( 3 1)

2bk+12

is true.

P(1)

(2)

(4)

3 1 = ( 1) k (a k + b k ) 3 (3a k + b k )

b k +1 = 3a k + b k .

( 3 1) = (1) (a
] (a 3 b )
n

n 1

3 bn

3an2 bn2 = (1)n-12n .

an n, bn n

and

and an2 2bn2 = (1)n.


a12 2b12 = 12 2(1)2 = (1)1.

. . i.e. . an k, bn k and

ak+1 = ak + 2bk k + 2k = k + 1, by (1)

P(k + 1) .

= (1) k 1 a k 3 b k

3 + b n (1) n 1

bk+1 = ak + bk

. . i.e. .

(3)
n

where a1 = 1, b1 = 1.

a k +1 = a k + b k ,

For P(1),
where a1 = 1 1 b1 = 1 1.
P(1) is true.

Also,

2n = (1)n-1 (3an2 bn2)

ak+12

3 b1

Let P(n) be the proposition

For

, where

= (1) k 1 a k 3 b k

Assume P(k)

k +1 by ( 2 )

3 + 1 = a n 3 + bn

(3) (4),

11

is true for some

= (1) k a k +1 3 b k +1
(iii)

b n+2 = 2(bn+1 + bn)

( 3 1) = (1) (a
1

Assume P(k)
For

ak2 2bk2 = (1)k.

(1)

and k 1 .

k + k = k + 1, by (1) and k 1 .

= (ak + 2bk) 2(ak + bk) = ( 1) (ak2 2bk2 ) = ( 1) ( 1)k =( 1)k+1 , by (1)

P(k + 1) is true.

By the principle of mathematical induction, the proposition is true n

.
3

(ii)

n is odd, then an2 2bn2 = 1,

If
2

an
<2
2
bn

If

an

bn

an2 2bn2 = 1,

a 2b n
a

lim n 2 = lim n
n b
n
bn
n

<

an , bn as n .

2
2

( 1)n
= lim a n 2b n
= lim
=0
n b a + 2 b
n
b n a n + 2b n
n
n
n

lim

an
bn

= 2

)(

a + 2b n 2 a n 2 b n
1 2 a n 2b n
a n +1
a + 2b n
1 2 a n
2 = n
2 = n
=
=
2
an
b
b n +1
a n + bn
a n + bn
a n + bn
+1 n
bn
an
2
bn

since

x n = x n 1 y n 1 , y n =

and since bn2 > 0,

a n +1 a n + 2b n
=
b n +1
a n + bn

6.

an2 = 2bn2 + 1 > 2bn2

an
> 2
bn

Since an n, bn n , therefore

(iii)

and since bn2 > 0,

< 2

is even, then

an
>2
2
bn

an2 = 2bn2 1 < 2bn2

xn yn

1 2 < 1

and

an
> 0,
bn

an
+1 > 1
bn

x n 1 + y n 1
x + y n 1
1
y n x n = n 1
x n 1 y n 1 =
2
2
2

x n 1 x n 1

) 0
2

for n > 1.